PENJADWALAN PROYEK PENGADAAN BANGUNAN PRASARANA RUANG ISOLASI PENYAKIT INFEKSI EMERGENCING (PIE) RSUD PROF. DR. ALOEI SABOE - Rachman, Ari Putra; Ngabito, Zulkifli (Universitas Bina Taruna Gorontalo, 2021)
Abstract: Project control is very important in the work process. This research will examine project scheduling for the construction of infrastructure for the isolation room for emerging infectious diseases (PIE) at Prof.H. Aloe Saboe hospital at Gorontalo City. This research used the Microsoft Project application method with data collected from interviews and documentation. The research results show that time scheduling using this application can be planned by producing days from the initial project planning, namely 150 days to 212 working days.